Variation in the distribution of Corbicula species (Mollusca: Bivalvia: Corbiculidae) after 25 years of its introduction in the Río de la Plata, Argentina - Reshaid, Yamila Verónica (2017)
In 1981, Corbicula fluminea (Müller, 1774) and C. largillierti (Philippi, 1844) were recorded at the Río de la Plata River. During the 1980’s, C. largillierti was found on a continuous fringe in the shore of that river, while C. fluminea was only found North of Buenos Aires’ harbor. Ten years later, C. fluminea spread to Punta Indio, while C. largillierti remained restricted to tributary streams. The density and size frequency distribution of both species were compared with previous data from samples performed in the same area in 1985–1989. The aim of this research was to determine whether the densities of both species decreased; whether C. fluminea is still more abundant than C. largillierti; and whether the size frequency distributions indicate different population structures from those observed in the end of the 1980’s. Nine localities from the river shore were sampled, and each individual was identified and measured. The size of C. fluminea varied between 2 and 39 mm, showing the highest frequency of individuals between 20 and 25 mm; furthermore the density decreased 90% in 2015/2016. No specimens of C. largillierti were found. In conclusion, the populations of Corbicula inhabiting the Río de la Plata River are retracting.